Hydrothermal pretreatment of fresh forest residues: Effects of feedstock pre-drying. (February 2016) - Bach, Quang-Vu; Tran, Khanh-Quang; Skreiberg, Øyvind
Abstract: Hydrothermal pretreatment has become an attractive method for upgrading biomass fuel because of its capacity to work effectively with various types of low cost wet feedstock. However, most of the past studies in the field dried the feedstock prior to the pretreatment without being aware of the effect of high temperature drying. In this study, fresh forest residues (Norway spruce and birch branches) were used as feedstocks to utilize the advantage of the hydrothermal pretreatment method. More importantly, the present work aims at investigating the effects of the pre-drying process on the solid product via a direct comparison on the fuel and physicochemical properties of hydrochars produced from fresh and dried forest residues. This assessment helps to identify differences when fresh and dried feedstocks are used for hydrothermal pretreatment study. The results showed that these differences were considerable with respect to solid and energy yields; and the use of dried feedstocks will be less representative for a commercially feasible hydrothermal process, using wet feedstock directly. Highlights: Dried feedstocks are more reactive than fresh feedstocks due to changes in the microstructure. The difference in solid yield between fresh and dried feedstocks is up to 9.7%. The difference in energy yield between fresh and dried feedstocks is up to 11.4%.